Public and private learning from prices, strategic substitutability and complementarity, and equilibrium multiplicity - Carolina Manzano; Xavier Vives (Center for Economic Studies and ifo Institute (CESifo), 2010)
We study a general static noisy rational expectations model, where investors have private information about asset payoffs, with common and private components, and about their own exposure to an aggregate risk factor, and derive conditions for existence and uniqueness (or multiplicity) of equilibria. We find that a main driver of the characterization of equilibria is whether the actions of investors are strategic substitutes or complements. This latter property in turn is driven by the strength of a private learning channel from prices, arising from the multidimensional sources of asymmetric information, in relation to the usual public learning channel. When the private learning channel is strong (weak) in relation to the public we have strong (weak) strategic complementarity in actions and potentially multiple (unique) equilibria. The results enable a precise characterization of whether information acquisition decisions are strategic substitutes or complements. We find that the strategic substitutability in information acquisition result obtained in Grossman and Stiglitz (1980) is robust.
Keywords: D82; D83; G14; 330; rational expectations equilibrium; strategic complementarity; multiplicity of equilibria; asymmetric information; risk exposure; bedging; supply information; Effizienzmarktthese; Anlageverhalten; Rationale Erwartung; Gleichgewicht; Informationsverhalten; Lernprozess; Asymmetrische Information; Spieltheorie; Theorie